Analisis Faktor-Faktor yang Mempengaruhi Terjadinya Kecenderungan Kecurangan (Fraud) di Sektor Pemerintah (Studi pada Pegawai Keuangan Pemerintah Kabupaten Banyuwangi) - Dini Eka Permatasari; Taufik Kurrohman; Kartika Kartika (STIE Indonesia Banking School, 2017)
This study aims to investigate perceptions of financial officers regarding the effectiveness of internal control systems, compensation allegiance, organizational culture, unethical behavior, leadership style, law enforcement, and information asymmetry against fraud incidents in the governmental sector. This research is using purposive sampling method. Data are collected by questionnaires. Respondents of this study are 32 financial officers in the Government of Banyuwangi Regency. Hypotheses are tested by using multiple linear regression. The result shows that there is no effect of the effectiveness of internal control system, compensation and information asymmetry to fraud on the financial officers of the Government of Banyuwangi Regency. Organizational culture, leadership style, and law enforcement have the negative effect of fraud on financial officers of Banyuwangi Regency Government. Unethical behavior has the positive effect on the tendency of fraud on the financial officers of the Government of Banyuwangi Regency.